Defoe and Scottish politics after union - Gathorne, R (Rhodes University, Faculty of Humanities, Department of History, 1954)
It would indeed have been a difficult matter for anybody possessing a taste for self-expression, a facility with words and an insatiable imagination to avoid becoming involved in political controversy in England during the early part of the Eighteenth Century. For one who, in addition, was confident in his ability to solve problems of state of whatever complexity it was clearly an impossibility. Daniel Defoe's close connection with politics during the first years of the Eighteenth Century involved him in numerous hardships. In later years it brought him much less fame than his excursions into fiction; but it was the means of providing him, albeit sparsely at times, with sufficient money to keep his creditors at bay. On more than one occasion the protection he gained helped to rescue him from imprisonment. Intro., p. 1.
Keywords: Defoe, Daniel, 1661?-1731 -- Political and social views; Scotland -- History -- 1689-1745